Glycobiology Protocols
DOI: 10.1385/1-59745-167-3:359
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Inhibition Assays for Siglecs

Abstract: Protein-carbohydrate interactions are believed to be important in many biological processes involving cellular communication. Although many of the experimental approaches for studying protein-carbohydrate interactions are similar to those commonly employed in protein-protein interactions, several important aspects have to be taken into account in binding assays with lectin-like receptors such as Siglecs, sialic acid-recognizing immunoglobulin-like lectins. This chapter describes experimental approaches using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…Inhibition assays for siglecs have been described (Bock & Kelm, 2006). Fetuin, containing both a2,3-and a2,6-linked Sia, was immobilized to a high binding microtitre plate as target glycoconjugate to determine siglec binding, whereas the compounds to be tested are used as competitive inhibitors.…”
Section: Inhibition Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition assays for siglecs have been described (Bock & Kelm, 2006). Fetuin, containing both a2,3-and a2,6-linked Sia, was immobilized to a high binding microtitre plate as target glycoconjugate to determine siglec binding, whereas the compounds to be tested are used as competitive inhibitors.…”
Section: Inhibition Assaysmentioning
confidence: 99%
“…For this, all samples were diluted two-fold in the final assay mixture, e.g., the stock solution of 10 mg mL À1 would lead to a final sample concentration of 5 mg mL À1 . Bound siglecs were quantified by using fluorescein diphosphate (FDP) as substrate (Bock & Kelm, 2006). Unspecific binding was determined using immobilized asialofetuin as target and subtracted.…”
Section: Inhibition Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins were analysed by ELISA for detecting the Fc part, a binding assay with immobilized fetuin and SDS-PAGE to verify the Sia binding activity. [94] Heterologous Expression and Purification of Myristoylated Recoverin: Expression of recombinant recoverin was essentially done as described previously. [95] Briefly, Escherichia coli strain BL21 was cotransformed with plasmids pET11d and pBB131 containing the genes for recoverin and yeast N-myristoyl-transferase (kind gift of Dr. Jeffrey Gordon), respectively.…”
mentioning
confidence: 99%
“…This is in agreement with our finding that the α2-6-sialylated N-glycans derived from bovine milk protein concentrate are more abundant than α2-3-sialylated N-glycans by about 36.2 molar percent, and they are composed of Neu5Ac/ Neu5Gcα2-6Gal1-4GlcNAc and Neu5Acα2-6GalNAc1-4GlcNAc. Previous studies also showed that N-glycans derived from bovine IgM, present in bovine whey [25], mainly terminated with Neu5Ac/Neu5Gcα2-6Gal [26]. These α2-6-linked sialylated glycans could be useful for determination of human-adapted influenza viruses and for study of the properties of several human cancers, including colon, breast and cervix cancers, associated with Siaα2-6Gal1-4GlcNAc level on their cell surface [19,27].…”
Section: Gu (Ods)mentioning
confidence: 90%